Determination of the optimum concentration of three cryoprotectants for the criopreservation of alpaca epididymal spermatozoa - Choez A., Katherine (2017)
The aim of this study was to determine the optimal concentration of glycerol, ethylene glycol and dimethyl sulfoxide (DMSO) in the cryopreservation of epididymal spermatozoa of alpaca. The effect of different concentrations of glycerol, ethylene glycol and DMSO: T1 (0 M), T2 (0.25 M), T3 (0.5 M), T4 (0.75 M), T5 (1 M), T6 (1.25 M), T7 (1.5 M) and T8 (1.75 M) was evaluated. A polynomial regression model was used to determine the best concentration of each cryoprotectant, resulting 1.16, 1.02 and 0.9 M the optimal concentrations for glycerol, ethylene glycol and DMSO respectively. In Experiment 2, the effect of the optimal concentrations between glycerol, ethylene glycol and DMSO on motility, plasma membrane integrity, and acrosomal viability and integrity in alpaca epididymal spermatozoa were analyzed. The results showed a mean of 35.8, 51.8 and 38.3% for DMSO and 30.8, 45.0 and 33.8% for glycerol for motility, plasma membrane integrity and acrosome viability and integrity, respectively, and without significant differences between these cryoprotectants. However, the results were significantly better (p<0.05) than for ethylene glycol (1.02 M). It is concluded that the concentrations of 0.9 M DMSO and 1.16 M glycerol better preserved the functional characteristics of alpaca epididymal spermatozoa as compared to ethylene glycol (1.02 M).